Estilos de vida saludables de niños, niñas y adolescentes (2017)
Objective: To describe the healthy lifestyles of children and adolescents in Barranquilla. Materials and methods: descriptive cross-sectional study in 991 children and adolescents. Physical activity was assessed using the Physical Activity Questionnaire for Adolescents and school children; a survey that measured the knowledge and practices of school oral health, hand washing, eating fruits and vegetables and postural care was applied; the Checklist “My Life in School”, which evaluates rates bullying and aggression; and emotional intelligence through the TMMS-24 scale. Results: The 65.4% were categorized as physically inactive. Only 14.7 % of students recognize that the maximum weight of the bag is 10% of their body weight; 34.1% change the toothbrush every three months as recommended by experts and 48,4% % brushes his teeth between 2 and 3 times a day; 16.6 % do not wash their hands before and after using the toilet and 9.4 % do not have before and after meals; 17.5 % have a good intake of vegetables and fruits; Index bullying and was found in 55.6 % of participants. Conclusion: The above results raise require interventions that increase healthy practices in children and adolescents. © 2017, Universidad del Norte. All rights reserved.